Fixed Target Program at the LHC - Di Nezza, P.; Carassiti, V.; Ciullo, G.; Engels, R.; Lenisa, P.; Pappalardo, L. L.; Santimaria, M.; Steffens, Erhard; Tagliente, G. (Proceedings of Science, 2024)
Collisions provided by a TeV-scale beam at the LHC on a fixed target will explore a unique kinematic region that has been poorly probed until now. Furthermore, advanced detectors make available probes that have never been accessed before. The LHCb spectrometer possesses the unique capability to function as a fixed-target experiment by injecting gas into the LHC beampipe while proton or ion beams are circulating. The resulting beam-gas collisions cover an unexplored energy range above that of previous fixed-target experiments but below the energies of the RHIC or LHC collider. In light of this, the LHCspin project aims to develop innovative solutions and cutting-edge technologies to access the field of spin physics over the next few years. This will be achieved by exploring a unique kinematic regime and exploiting new reaction processes. To accomplish this goal, a polarized gaseous target will be operated in combination with the high-energy, high-intensity LHC beams and the highly performing LHCb particle detector. This configuration has the potential to open new physics frontiers and deepen our understanding of the intricacies of strong interaction in the non-perturbative regime of QCD. With center-of-mass energies per nucleon up to 115 GeV and utilizing both proton and heavy-ion beams, this setup covers a wide backward rapidity region, including the poorly explored high Bjorken-x and high Feynman-x regimes. This ambitious task is based on the recent installation of an unpolarized gas target (SMOG2) in the LHCb spectrometer. This setup not only constitutes a unique project but also provides an invaluable platform for its polarized upgrade. This article offers an overview of the physics potential, a description of the LHCspin experimental setup, and details the initial findings from the SMOG2 system.
CRIS-Team Scopus Importer:2025-02-04

High-density gas target at the LHCb experiment - Garcia, O. Boente; Bregliozzi, G.; Calegari, D.; Carassiti, V.; Ciullo, G.; Coco, V.; Collins, P.; Pinto, P. Costa; De Angelis, C.; Di Nezza, P.; Dumps, R.; Ferro-Luzzi, M.; et al. (Physical Review Accelerators and Beams, 2024)
The recently installed internal gas target at LHCb presents exceptional opportunities for an extensive physics program for heavy-ion, hadron, spin, and astroparticle physics. A storage cell placed in the LHC primary vacuum, an advanced Gas Feed System, the availability of multi-TeV proton and ion beams, and the recent upgrade of the LHCb detector make this project unique worldwide. In this paper, we outline the main components of the system, the physics prospects it offers, and the hardware challenges encountered during its implementation. The commissioning phase has yielded promising results, demonstrating that fixed-target collisions can occur concurrently with the collider mode without compromising efficient data acquisition and high-quality reconstruction of beam-gas and beam-beam interactions.
CRIS-Team Scopus Importer:2024-11-29

LHCspin: A polarized internal target for the LHC - Lenisa, Paolo; Steffens, Erhard; Carassiti, Vito; Ciullo, Giuseppe; Di Nezza, Pasquale; Pappalardo, Luciano Libero; Vasilyev, Alexander (Proceedings of Science, 2019)
The LHCspin project aims to bring both unpolarized and polarized physics at the LHC through the installation of a gaseous fixed target at the upstream end of the LHCb detector. The forward geometry of the LHCb spectrometer (2 < η < 5) is perfectly suited for the reconstruction of particles produced in fixed-target collisions. The fixed-target configuration, with center-of-mass energies ranging from √sNN = 72 GeV in collisions with Pb beams to √s = 115 GeV in pp interactions, allows to cover a wide backward center-of-mass rapidity region, corresponding to the poorly explored high x-Bjorken and high x-Feynman regimes. The use of transversely polarized H and D targets will allow to study the quarks TMDs in p-p collisions at unique kinematic conditions. Furthermore, being LHCb specifically designed for heavy-flavor physics, final states with c- or b-quarks (e.g. inclusive quarkonia production) will be efficiently reconstructed, thus providing, among other fundamental measurememnts, access to the so-far unknown gluons TMDs. The contribution focuses on the design considerations of the polarized internal target and on a discussion of possible critical machine issues.
CRIS-Team Scopus Importer:2024-12-16

LHCspin: Unpolarized gas target SMOG2, and prospects for a polarized gas target at the LHC - Steffens, Erhard; Di Nezza, P.; Santimaria, M.; Carassiti, V.; Ciullo, G.; Lenisa, P.; Pappalardo, L. L.; Tagliente, G. (Proceedings of Science, 2023)
The status of the first phase of LHCspin is discussed, based on an unpolarized gas target - SMOG2 -, an upgrade of the previous SMOG system. It consists of an openable 20 cm long storage tube in front of the VELO detector. A known gas flow from a gas feed system is injected into the tube's center, producing a localized triangular density distribution. First tests of the SMOG2 system with LHC beam and H2, He, Ne and Ar gas have been performed. The target system and the precision for setting the target areal density are presented. - In the second part, design considerations for a polarized gas target at the LHC are presented. The fact that the initial tests worked as expected is a strong confirmation that the storage cell/tube is a viable concept compatible with LHC conditions. For the beam stability, very few coatings of surfaces close to the LHC beam are accepted. The SMOG2 cell is coated with amorphous Carbon (a-C). It is an open question whether this coating might be used for a polarized target cell. In order to circumvent the coating problem, a free-beam PGT within the present VELO-vessel has been presented. This could be a reasonable starting point for a Spin program at the LHC.
CRIS-Team Scopus Importer:2023-09-15

Longitudinal double-spin asymmetries in semi-inclusive deep-inelastic scattering of electrons and positrons by protons and deuterons - Airapetian, A.; Akopov, N.; Akopov, Z.; Aschenauer, E. C.; Augustyniak, W.; Avakian, R.; Avetissian, A.; Belostotski, S.; Blok, H. P.; Borissov, A.; Bryzgalov, V.; Capitani, G. P.; et al. (Physical Review D, 2019)
A comprehensive collection of results on longitudinal double-spin asymmetries is presented for charged pions and kaons produced in semi-inclusive deep-inelastic scattering of electrons and positrons on the proton and deuteron, based on the full HERMES data set. The dependence of the asymmetries on hadron transverse momentum and azimuthal angle extends the sensitivity to the flavor structure of the nucleon beyond the distribution functions accessible in the collinear framework. No strong dependence on those variables is observed. In addition, the hadron charge-difference asymmetry is presented, which under certain model assumptions provides access to the helicity distributions of valence quarks.
CRIS-Team WoS Importer:2019-06-21

Low-energy spin-physics experiments with polarized beams and targets at the COSY storage ring - Lenisa, Paolo; Rathmann, F.; Barion, L.; Barsov, S.; Bertelli, S.; Carassiti; Ciullo, G.; Contalbrigo, M.; Ramusino, A. Cotta; Dymov, S.; Engels, Ralf; Eversheim, D.; et al. (EPJ Techniques and Instrumentation, 2019)
A low-energy spin-physics program is being developed at the COSY storage ring. To support the planned experimental activities, several experimental tools for polarized beams and targets have been developed. The paper presents the physics case and the readiness of the setup for its realization.
CRIS-Team WoS Importer:2021-10-18

The HERMES experiment: A personal story - Milner, Richard; Steffens, Erhard (World Scientific Publishing Co. Ltd., 2021)
This book describes the story of how a collaboration of several hundred physicists from Europe and North America formed in 1988 to design, construct, install, commission and operate, for the years 1995-2007 the technically innovative HERMES experiment at the DESY laboratory in Hamburg, Germany to study the spin structure of the fundamental structure of matter. The authors begin by introducing the fascinating world of subatomic physics and relate their personal story of how the HERMES experiment came about. Guided by the exciting idea to use a new type of target internal to an electron storage ring, the HERMES collaboration was born to realize this innovative experimental approach at the new HERA accelerator at DESY. The book describes the technical design of HERMES; the successful effort to secure the necessary funds to construct the experiment in different countries; the fabrication of the different components by the different HERMES institutes; and the story of the installation and commissioning of HERMES in the East Hall of HERA in the hot summer of 1995. Until 2007, when the operation of HERA ceased, the collider ran typically about 9 months per year continuously, during which HERMES data taking shifts were manned to ensure that data of the highest quality were acquired. The book describes the HERMES scientific results, their considerable impact, how HERMES shaped an entire generation of young people into scientific leaders, and ends with a description of the twenty-first century picture of the proton that has subsequently been developed.
CRIS-Team Scopus Importer:2021-09-10

THE LHCspin PROJECT: A POLARISED GAS TARGET AT THE LHC - Santimaria, Marco; Carassiti, Vittore; Ciullo, Giuseppe; Di Nezza, Pasquale; Lenisa, Paolo; Mariani, Saverio; Pappalardo, Luciano Libero; Steffens, Erhard (Acta Physica Polonica B, Proceedings Supplement, 2025)
LHCb is the only experiment at the LHC able to reconstruct simultaneously events from beam–beam and beam–gas collisions taking place in a gas storage cell. The aim of the LHCspin project is to bring spin physics at the LHC for the first time by injecting polarised hydrogen and deuterium. This would enable the high-energy LHC beam and the peculiar forward geometry of LHCb to explore the 3D structure of matter in a unique kinematic regime and by means of probes that are not accessible in other facilities.
CRIS-Team Scopus Importer:2025-04-01

THE LHCspin PROJECT - Di Nezza, P.; Carassiti, V.; Ciullo, G.; Lenisa, P.; Pappalardo, L. L.; Santimaria, M.; Steffens, Erhard; Tagliente, G. (2023)
The goal of LHCspin is to develop innovative solutions and cutting-edge technologies to access the field of spin physics over the next few years by exploring a unique kinematic regime and exploiting new reaction processes. To this end, a polarized gaseous target, operated in combination with the high-energy, high-intensity LHC beams and the highly performing LHCb particle detector, has the potential to open new physics frontiers and deepen our understanding of the intricacies of the strong interaction in the non-perturbative regime of QCD. This configuration, with center-of-mass energies per nucleon up to 115 GeV, using both proton and heavy-ion beams, covers a wide backward rapidity region, including the poorly explored high Bjorken-x and high Feynman-x regimes. This ambitious task is based on the recent installation of an unpolarised gas target (SMOG2) in the LHCb spectrometer. This setup not only constitutes a unique project but also provides an invaluable playground for its polarized upgrade. This article provides an overview of the physics potential, a description of the LHCspin experimental setup, and the first output of the SMOG2 system.
CRIS-Team Scopus Importer:2024-12-16

The LHCspin project - Pappalardo, L. L.; Carassiti, V.; Di Nezza, P.; Ciullo, G.; Lenisa, P.; Steffens, Erhard; Vasilyev, A. (Proceedings of Science, 2019)
The LHCspin project aims to bring both unpolarized and polarized physics at the LHC through the installation of a gaseous fixed target at the upstream end of the LHCb detector. The forward geometry of the LHCb spectrometer (2 < η < 5) is perfectly suited for the reconstruction of particles produced in fixed-target collisions. The fixed-target configuration, with center-of-mass energies ranging from √sNN = 72 GeV in collisions with Pb beams to √s = 115 GeV in pp interactions, allows to cover a wide backward center-of-mass rapidity region, corresponding to the poorly explored high x-Bjorken and high x-Feynman regimes. The project has several ambitious goals regarding heavy-ion physics and new-era quantitative searches in QCD through the study of the nucleon's internal dynamics in terms of both quarks and gluons degrees of freedom. In particular, the use of transversely polarized H and D targets will allow to study the quarks TMDs in pp collisions at unique kinematic conditions. Furthermore, being LHCb specifically designed for heavy-flavor physics, final states with c- or b-quarks (e.g. inclusive quarkonia production) will be efficiently reconstructed, thus providing, among other fundamental measurememnts, access to the so-far unknown gluons TMDs. The status of the project is presented along with a selection of physics opportunities.
CRIS-Team Scopus Importer:2019-12-24